The Anti-hero in the American Novel From Joseph Heller to Kurt Vonnegut - Simmons, David 1979- (American Literature Readings in the 21st Century, 2008)
The Anti-Hero in the American Novel rereads major texts of the 1960s to offer an innovative re-evaluation of a set of canonical novels that moves beyond entrenched post-modern and post-structural interpretations towards an appraisal which emphasizes the specifically humanist and idealist elements of these works